Lipid Profiles in Patients With Ulcerative Colitis Receiving Tofacitinib—Implications for Cardiovascular Risk and Patient Management. Issue 6 (1st September 2020) - Sands, Bruce E; Colombel, Jean-Frédéric; Ha, Christina; Farnier, Michel; Armuzzi, Alessandro; Quirk, Daniel; Friedman, Gary S; Kwok, Kenneth; Salese, Leonardo; Su, Chinyu; Taub, Pam R
Abstract: Background: Patients with ulcerative colitis (UC) are at elevated risk of cardiovascular disease vs the general population, despite a lower prevalence of traditional risk factors, including hyperlipidemia. Mechanistic studies in patients with rheumatoid arthritis and psoriasis suggest that tofacitinib restores serum lipids to preinflammation levels by reversing inflammation-induced cholesterol metabolism changes. We reviewed data on lipid levels and cardiovascular events, alongside recommendations for managing lipid levels during tofacitinib treatment in patients with UC, based on up-to-date expert guidelines. Methods: Data were identified from a phase 3/open-label, long-term extension (OLE) tofacitinib UC clinical program (cutoff May 27, 2019). Literature was identified from PubMed (search terms "lipid, " "cholesterol, " "lipoprotein, " "cardiovascular, " "inflammation, " "atherosclerosis, " "tofacitinib, " "rheumatoid arthritis, " "psoriasis, " "inflammatory bowel disease, " "ulcerative colitis, " "hyperlipidemia, " and "guidelines") and author knowledge. Data were available from 4 phase 3 clinical trials of 1124 patients with moderately to severely active UC who received ≥1 dose of tofacitinib 5 or 10 mg twice daily in induction (two identical trials), maintenance, and OLE studies (treatment duration ≤6.8 years; 2576.4 patient-years of drug exposure). Results: In the OLE study, tofacitinib treatment was not associated with major changes from baseline in total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglycerides, total cholesterol/high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol/high-density lipoprotein cholesterol, with lipid levels and ratios generally remaining stable over time. The major adverse cardiovascular events incidence rate was 0.26/100 patient-years (95% confidence interval, 0.11-0.54). Conclusions: Lipid levels and ratios remained generally unchanged from baseline in the OLE study after tofacitinib treatment, and major adverse cardiovascular events were infrequent. Long-term studies are ongoing. ClinicalTrials.gov identifiers: NCT01465763, NCT01458951, NCT01458574, NCT01470612